THE ROLE OF CAPITAL MARKETS AND CAPITAL INVESTMENTS IN ECONOMIC GROWTH: THE EXPERIENCE OF UZBEKISTAN AND EUROPEAN COUNTRIES - Gulshoda Nuriddinova; Sevara Eshqobulova (Modern American Journals, 2025)
This paper examines the impact of capital markets and capital investments on economic growth through a comparative analysis of Uzbekistan and European countries. The aim of the study is to empirically assess the effect of capital market development on economic growth and to identify effective policy and institutional directions for Uzbekistan.
Keywords: Capital market, capital investments, economic growth, financial system, investment efficiency, European experience, Uzbekistan, empirical analysis, regression model, institutional development.